2022
DOI: 10.1371/journal.pone.0262009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ARIMA and LSTM for prediction of hemorrhagic fever at different time scales in China

Abstract: Objectives This study intends to build and compare two kinds of forecasting models at different time scales for hemorrhagic fever incidence in China. Methods Autoregressive Integrated Moving Average (ARIMA) and Long Short-Term Memory Neural Network (LSTM) were adopted to fit monthly, weekly and daily incidence of hemorrhagic fever in China from 2013 to 2018. The two models, combined and uncombined with rolling forecasts, were used to predict the incidence in 2019 to examine their stability and applicability.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Both ARIMA and LSTM models showed the same trends. However, LSTM is a model that can learn the long-term dependencies, and it can remember the information that is processed in the model for a very long time [22]. In terms of computational time, the ARIMA models consume more time when using the rolling forecast method, and it is unfeasible to train new models when the orders of p, d, and q increase [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both ARIMA and LSTM models showed the same trends. However, LSTM is a model that can learn the long-term dependencies, and it can remember the information that is processed in the model for a very long time [22]. In terms of computational time, the ARIMA models consume more time when using the rolling forecast method, and it is unfeasible to train new models when the orders of p, d, and q increase [34].…”
Section: Discussionmentioning
confidence: 99%
“…LSTM has been extensively utilized in time series prediction in [17][18][19][20][21]. Autoregressive integrated moving average (ARIMA) is also another forecasting model [22] that predicts the future values based on the past values. ARIMA is the best model for one-step out-of-sample forecasting and is good for the data which consist of linear and short-term dependency (weekly or hourly) [23].…”
Section: Introductionmentioning
confidence: 99%
“…We then further constructed the multivariable LSTM model, i.e., adding meteorological factors with lagged effects to the LSTM model, and the results obtained showed that the meteorological factors could improve the performance of the LSTM model, but it was still worse than the ARIMA/ARIMAX model and Holt-Winters model. The LSTM model is a complex neural network that requires a large amount of data for training, and too few training samples can lead to overfitting [ 43 ]. In this study, we are constructing a time series forecasting model based on monthly data from 2010 to 2019, with a small sample size and strong linear dependence between series; so, the ARIMA/ARIMAX model and Holt-Winters model will perform better when they have a clear trend in the series.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have just started to be applied in the prediction analysis of deformation time series 12,13 . Having outstanding performance, Autoregressive Integrated Moving Average (ARIMA), which is a traditional stochastic approach, and Long Short Term Memory (LSTM) methods were compared in many studies, and different results were achieved 14,15,16 .…”
Section: Introductionmentioning
confidence: 99%